The Role and Significance of EU Guidelines on Non-financial Reporting for SMEs - Modrzyński, Paweł; Voss, Grażyna (Comparative Economic Research. Central and Eastern Europe, 2025)
This study investigates the role and impact of non-financial reporting (NFR) regulations on small and medium-sized enterprises (SMEs) in the European Union. While large enterprises are the primary focus of directives such as the Non-Financial Reporting Directive (NFRD) and the Corporate Sustainability Reporting Directive (CSRD), SMEs are increasingly affected due to supply chain dependencies and financial incentives. The research aims to assess SME awareness, challenges, and expected benefits related to NFR adoption. The study is based on an empirical survey of 151 SMEs in the Kuyavian-Pomeranian Voivodeship in Poland, utilizing statistical methods such as correlation analysis and regression modeling to evaluate attitudes toward compliance and perceived barriers. The findings reveal that while SMEs acknowledge the growing relevance of NFR, resource limitations and lack of expertise hinder effective implementation. Nevertheless, SMEs that have proactively adopted NFR practices report benefits, including enhanced stakeholder relationships and a competitive market advantage. The study highlights the necessity for targeted policy interventions, including financial support, simplified compliance frameworks, and dedicated training initiatives to facilitate SME adaptation to sustainability reporting standards. This research contributes to the ongoing discussion on sustainability reporting by focusing on SMEs, a sector often neglected in NFR policy discussions. The study also provides empirical insights into how regulatory developments shape SME behavior, offering recommendations for policymakers on supporting sustainability transitions in the SME sector.